Sidenafil Pre-Treatment Promotes Decompression Sickness in Rats - Blatteau, Jean-Eric (Public Library of Science, 2013)
Vascular bubble formation after decompression contributes to endothelial injuries which form the basis for the development of decompression sickness (DCS). Nitric oxide (NO) is a powerful vasodilator that contributes to vessel homeostasis. It has been shown that NO-releasing agent may reduce bubble formation and prevent serious decompression sickness. The use of sildenafil, a well-known, phosphodiesterase-5 blocker, which act by potentiating the vasodilatory effect on smooth muscle relaxation, has never been studied in DCS. The purpose of the present study was to evaluate the clinical effects of sildenafil pre-treatment on DCS in a rat model. 67 rats were subjected to a simulated dive at 90 msw for 45 min before staged decompression. The experimental group received 10 mg/kg of sildenafil one hour before exposure (n = 35) while controls were not treated (n = 32). Clinical assessment took place over a period of 30 min after surfacing. At the end, blood samples were collected for blood cells counts and the level of circulating bubbles in the right cavities was quantified. There were significantly more manifestations of DCS in the sildenafil group than in the controls (34.3% vs 6.25%, respectively, p = 0.012). Platelet count was more reduced in treated rats than in controls (−21.7% vs −7%, respectively, p = 0.029), whereas bubble grades did not differ between groups. We concluded that pre-treatment with sildenafil promotes the onset and severity of neurological DCS. When considering the use of phosphodiesterase-5 blockers in the context of diving, careful discussion with physician should be recommended.